Evaluation Reaction Support Breaker Wave Floating on the System mooring Catenary with Variation Position Fairlead - Hotma Harapan Saragih; Roesdiman Sogiarso; Indra Noer Hamdhan (Politeknik Siber Cerdika Internasional, 2026)
Research This evaluate reaction support on the breaker wave floating measuring (55 × 30 × 10) m moored effective draft 5 m use chain catenary system studlink as many as 10 pieces (5 left + 5 right ). Analysis numeric done using SAP2000 for variation fairlead elevation z=-5,